The Effect of Interest Rates on Investment Decision-Making in the Banking Sector Listed on the Indonesia Stock Exchange - Nissa Septiyani Haris; Irwansyah Irwansyah; Lilis Marlina (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study aims to analyze the effect of interest rates on investment decisions in banking sector companies listed on the Indonesia Stock Exchange (IDX). Research Method: This research employs an associative quantitative approach using secondary data sourced from annual financial reports on the IDX and the BI 7-Day Reverse Repo Rate. Utilizing a saturated sampling technique, the entire population of 46 banking companies was selected as the sample. Data analysis was conducted using simple linear regression and hypothesis testing via IBM SPSS. Results and Discussion: The test results demonstrate that interest rates do not have a significant effect on investment decisions, which are proxied by the Price-Earnings Ratio (PER) (sig. value 0.558 > 0.05; R² = 0.002). This indicates that investors respond more to the company's internal fundamental factors than to fluctuations in the macroeconomic benchmark interest rate. Implications: These findings recommend that investors prioritize analyzing a company's financial fundamentals when making investment choices. Future studies are advised to include other macroeconomic variables or specific financial performance indicators. Originality: The novelty of this research lies in its comprehensive examination of the entire banking sector population on the IDX, specifically using PER as a proxy for investment decisions amid recent benchmark interest rate dynamics.